(untitled) (Docentes 2.0 Journal, 2021)
This article is derived on the academic experiences obtained in five diploma courses on theory, processes for writing scientific articles, design, structure and thesis writing, organized by the Self-Access Center of the Department of Languages (DI), at the Universidad Michoacana, San Nicolás de Hidalgo (UMSNH). This document showed that the multidisciplinary diploma courses in scientific writing seek to provide theoretical and methodological support to integrated students, guiding them towards legible writings of academic documents, using practical, technological, discursive, writing, style, including structure, editorial trends, so important in the dissemination of science within university communities. This, under the guidance of expert professors in different cultural areas, through an integral proposal, whose purpose is to support thesis students in their research: style, writing, grammar, technologies and languages. This proposal has yielded excellent results; it is expected to serve as a reference in other institutions. An action-research methodology of interpretative scope was used, giving tangible results to solve the needs of the teaching-learning process that allows the construction of scientific articles or theses. The above, synthesizing the information, was the result of 20 (twenty) diagnostic questionnaires, applied to students who entered diploma courses. The data from the survey show the category of style and writing as the greatest need of the students in scientific matters, therefore, it is affirmed that undergraduate and graduate students resort to the diploma courses not only to learn grammar and semantics, but also to adequately structure sentences and a discourse.